2022
DOI: 10.3390/nu14194170
|View full text |Cite
|
Sign up to set email alerts
|

Mulberrofuran G, a Mulberry Component, Prevents SARS-CoV-2 Infection by Blocking the Interaction between SARS-CoV-2 Spike Protein S1 Receptor-Binding Domain and Human Angiotensin-Converting Enzyme 2 Receptor

Abstract: Despite the recent development of RNA replication-targeted COVID-19 drugs by global pharmaceutical companies, their prescription in clinical practice is limited by certain factors, including drug interaction, reproductive toxicity, and drug resistance. COVID-19 drugs with multiple targets for the SARS-CoV-2 life cycle may lead to a successful reduction in drug resistance as well as enhanced therapeutic efficacy, and natural products are a potential source of molecules with therapeutic effects against COVID-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It was worth noting that mulberrofuran G ( 6 ) had been reported a lot from different Morus species since its first isolation from M. alba, and it exerted diverse biological properties including cyclic AMP phosphodiesterase inhibitory, antibacterial, cytotoxic, , tyrosinase inhibitory, antiviral, , cytoprotective, , protein tyrosine phosphatase 1B, and tyrosinase inhibitory activities, as well as inhibition against multiple targets of Alzheimer’s disease. , Also, it was reported to show potent α-glucosidase inhibitory effect . However, all of these previous biological tests were only conducted in vitro at molecular and cellular levels, with no in vivo evaluation recorded so far.…”
Section: Resultsmentioning
confidence: 99%
“…It was worth noting that mulberrofuran G ( 6 ) had been reported a lot from different Morus species since its first isolation from M. alba, and it exerted diverse biological properties including cyclic AMP phosphodiesterase inhibitory, antibacterial, cytotoxic, , tyrosinase inhibitory, antiviral, , cytoprotective, , protein tyrosine phosphatase 1B, and tyrosinase inhibitory activities, as well as inhibition against multiple targets of Alzheimer’s disease. , Also, it was reported to show potent α-glucosidase inhibitory effect . However, all of these previous biological tests were only conducted in vitro at molecular and cellular levels, with no in vivo evaluation recorded so far.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies showed that this natural compound inhibited the SARS-CoV-2 infection by interacting with both the viral spike proteins and the host ACE2 receptor cells with an IC 50 of 10.23 μM at a concentration of less than 50 μM. Furthermore, in silico studies demonstrated the more stable binding interactions of ligands with spike proteins compared to ACE2 receptors [ 63 ] ( Table 1 ).…”
Section: In Vitro and In Silico Studiesmentioning
confidence: 99%
“…Therefore, it is worthwhile to investigate the potential of certain biological response modifiers (BRMs) to boost the antiviral immune response and lower hospitalization risk. There have been earlier studies over an extensive range of natural products, herbal supplements, and traditional medicine products that have been reported to work against COVID-19 in vitro [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, we are not aware of an in vivo human study that was carried out showing the efficiency of a food supplement in exerting anti-COVID-19 effects, though vitamin C has been shown to shorten patient stays in intensive care units by 8.6% [ 29 ] and to shorten the period under mechanical ventilation by 18.2% [ 30 ].…”
Section: Introductionmentioning
confidence: 99%